“PROSPECTIVE OBSERVATIONAL STUDY OF PATTERN, SEVERITY AND OUTCOME OF DIFFERENT POISONING CASES IN TERTIARY CARE HOSPITAL OF EASTERN GUJARAT” (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute poisoning is a major public health problem and a common cause of emergency hospital admissions in developing countries. The pattern, severity, and outcomes of poisoning vary according to geographical region, socioeconomic conditions, and accessibility of toxic substances. Understanding these factors is essential for improving preventive strategies and patient management.The aim of the present study is to evaluate the pattern, severity, and outcomes of different poisoning cases admitted to a tertiary care hospital in Eastern Gujarat. Materials and Methods: A prospective observational study was conducted among 424 patients admitted with acute poisoning to a tertiary care hospital in Eastern Gujarat. Demographic characteristics, type and mode of poisoning, timing of exposure, severity at admission, duration of hospital stay, and clinical outcomes were recorded and analyzed using descriptive statistics. Results: The majority of patients belonged to the 21–30 years age group (35.14%) and were male (73.11%). Most patients were married (59.43%), and suicidal poisoning was the predominant mode of poisoning (79.95%). Pesticides and organophosphorus compounds were the most common poisoning agents (34.43%), followed by drug poisoning/drug overdose (29.72%). Most poisoning incidents occurred during evening and night hours (54.71%), and 46.69% of patients presented within 2–6 hours of exposure. Mild poisoning was observed in 59.90% of cases, while moderate and severe poisoning accounted for 26.18% and 13.92%, respectively. The majority of patients (75.94%) required hospitalization for ≤3 days. Regarding outcomes, 65.56% of patients were discharged, 18.16% left against medical advice (DAMA), and 16.27% died. Conclusion: Acute poisoning predominantly affected young adult males and was mainly associated with suicidal intent. Pesticides and organophosphorus compounds were the most common poisoning agents. Although most patients had mild poisoning and favorable outcomes, the substantial mortality observed highlights the need for improved poison prevention strategies, mental health interventions, early healthcare access, and prompt management to reduce poisoning-related morbidity and mortality.